2004
DOI: 10.1101/lm.66004
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Fear Expression in Trace and Delay Conditioning Measured by Fear-Potentiated Startle in Rats

Abstract: In two experiments, the time course of the expression of fear in trace (hippocampus-dependent) versus delay (hippocampus-independent) conditioning was characterized with a high degree of temporal specificity using fear-potentiated startle. In experiment 1, groups of rats were given delay fear conditioning or trace fear conditioning with a 3-or 12-sec trace interval between conditioned stimulus (CS) offset and unconditioned stimulus (US) onset. During test, the delay group showed fear-potentiated startle in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…It should be noted that equivalent rates of delay and trace conditioning and equivalent asymptotes, when the trace interval is short, have been reported by others. For example, Kehoe and Napier (1991), using rabbits, found similar rates of 400-ms delay and 400-ms trace eyeblink conditioning with a 300-ms trace interval and Burman and Gewirtz (2004) reported equivalent fear after 7-sec delay and 7-sec trace fear conditioning with a 3-sec trace interval when fear was assessed using fear-potentiated startle.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that equivalent rates of delay and trace conditioning and equivalent asymptotes, when the trace interval is short, have been reported by others. For example, Kehoe and Napier (1991), using rabbits, found similar rates of 400-ms delay and 400-ms trace eyeblink conditioning with a 300-ms trace interval and Burman and Gewirtz (2004) reported equivalent fear after 7-sec delay and 7-sec trace fear conditioning with a 3-sec trace interval when fear was assessed using fear-potentiated startle.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that having a delay between the CS and the US may result in an increase in anticipatory anxiety, since there is a period of potential uncertainty regarding whether the participant will get punished or not. Indeed, it has been shown that the delay between the CS and the US is a critical determinant of the time course of fear expression, and that after learning fear continues to be expressed after the presentation of the CS until the scheduled occurrence of the US (Burman and Gewirtz, 2004). Therefore, future work needs to directly compare the effect of different delay intervals on avoidance behavior, and how that may be expressed at the neuronal level.…”
Section: Controlmentioning
confidence: 97%
“…Cole, Barnet, and Miller (1995) have argued that the typically observed behavioral inferiority of trace, relative to shortdelay, conditioning reflects the expression of different temporal information encoded in the associations between CSs and USs, rather than inferior learning per se after trace conditioning (see also Burman & Gewirtz, 2004;Kehoe & Weidemann, 1999). Specifically, Cole et al suggested that rats learn ISIs between CSs and USs and that the learning of a long ISI (as in trace conditioning) is expressed as a behavioral deficit, and they provided evidence of substantial learning following trace conditioning when measured indirectly with second-order and sensory preconditioning.…”
Section: Discussionmentioning
confidence: 99%